WILLIAM SHAKESPEARE AS A NON-HEGEMONIC AUTHOR? SHAKESPEAREAN FORM AND THE POETICS OF EMULATION - João Cezar de Castro Rocha (Revista Brasileira de Literatura Comparada, 2024)
The omnipresence of William Shakespeare’s works is striking (although understandable) when it comes to the complex process of the self-definition of non-hegemonic cultures. After all, how to outline one’s own portrait when the model adopted implies the centrality of the other in defining the self? This is the inescapable predicament derived from the mimetic dimension of identity in non-hegemonic contexts and its vulnerability concerning the centrality of the other in shaping one’s own desire and self-image.